2008
DOI: 10.1016/j.jvs.2007.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of ruptured abdominal aortic aneurysms: A systematic review and meta-analysis

Abstract: Mortality in people who underwent REVAR is lower than that in historical reports of unselected people undergoing open repair. Further investigation is needed to determine whether the difference in mortality is attributable to patient selection alone or to this new approach to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 55 publications
4
96
0
1
Order By: Relevance
“…The first of the later randomised trials (AJAX) 19 The first results of 30-day mortality came from the Dutch trial (AJAX) in August 2013, 14,19 after recruitment to the IMPROVE trial had closed on 21 July 2013. AJAX reported a low 30-day mortality for both randomised groups (21% for the EVAR group and 25% for the open repair group; p = 0.66); however, this was a secondary outcome measure.…”
Section: Design Of the Recent Randomised Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of the later randomised trials (AJAX) 19 The first results of 30-day mortality came from the Dutch trial (AJAX) in August 2013, 14,19 after recruitment to the IMPROVE trial had closed on 21 July 2013. AJAX reported a low 30-day mortality for both randomised groups (21% for the EVAR group and 25% for the open repair group; p = 0.66); however, this was a secondary outcome measure.…”
Section: Design Of the Recent Randomised Trialsmentioning
confidence: 99%
“…When this trial was first discussed, observational studies (synthesised in systematic reviews [11][12][13][14] were reporting much lower 30-day mortality for endovascular repair of ruptured AAAs and some such studies 11 have suggested that this should become the new gold standard treatment of ruptured aneurysms without the need for a randomised trial. In addition, the in-hospital and 1-year costs of treating ruptured aneurysms by endovascular repair may be up to 40% lower than for treatment by open repair.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis in 2008 reported a 21% mortality rate with EVAR for RAAAs. 4) Furthermore satisfactory clinical results of 'EVAR-first protocol' has been increasingly reported. 5,6) Speicher et al reported that EVAR should be strongly considered for all RAAA patients with acceptable anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…Following aortic rupture, endovascular surgery has shown promise in reducing mortality. Mortality rates following EVAR for rAAA are less than 20% in several non-randomised studies [1,21,[34][35][36][37] and 17-30.2% in other large metaanalyses [2,[38][39][40][41]. However, randomised controlled trial (RCT) data are currently lacking.…”
Section: Suitability For Evarmentioning
confidence: 99%